Glaucous Gulls Kleptoparasiting Arctic Foxes in Magdalenefjorden, NW Spitsbergen - Stempniewicz, Lech; Iliszko, Lech (ARCTIC, 2010)
Observations were made of glaucous gulls (Larus hyperboreus) stealing little auks (Alle alle) stored in a den by arctic foxes (Vulpes lagopus) in Magdalenefjorden, northwest Spitsbergen. Before stealing the spoil, the gulls observed and followed foxes transporting little auks hunted in a nearby colony. Skill in detecting and successfully taking over the food cached by arctic foxes may help glaucous gulls to survive critical periods of lowered prey availability and enhanced energy demands, such as the little auk incubation period, when the auks are well hidden in the nests and inaccessible for gulls feeding their own large nestlings. These observations are the first documented instances of the glaucous gulls kleptoparasiting arctic foxes and provide additional evidence of the complex nature of interactions occurring between these two opportunistic Arctic predators. On a observé des goélands bourgmestres (Larus hyperboreus) en train de voler des mergules nains (Alle alle) qui avaient été placés dans une tanière par des renards arctiques (Vulpes lagopus) à Magdalenefjorden, dans le nord-ouest de Spitsbergen. Avant de voler les mergules, les goélands observaient les renards et les suivaient en train de transporter les mergules nains chassés dans une colonie située tout près. L’aptitude à détecter la nourriture cachée par les renards arctiques et à s’en accaparer pourrait aider les goélands bourgmestres à survivre pendant les périodes critiques où il y a peu de proies et où le besoin en énergie est plus grand, telle que la période d’incubation des mergules nains, soit lorsque les mergules sont bien cachés dans les nids et qu’ils ne sont pas accessibles aux goélands qui nourrissent leurs propres nichées d’envergure. Ces observations constituent les premiers cas documentés de goélands bourgmestres en train de faire du cleptoparasitisme chez le renard arctique, en plus de présenter des preuves supplémentaires de la nature complexe des interactions entre ces deux prédateurs opportunistes de l’Arctique.